Development of Basic Science Concept Teaching Materials Integrating Project-Based Inquiry Models to Improve Science Process Skills - Kiki Pratama Rajagukguk; Nurul Hasanah; Elfi Lailan Syamita Lubis; Aisah (UNIVERSITAS NEGERI MEDAN, 2026)
This research aimed to develop and evaluate Basic Science Concepts instructional materials integrating a project-based inquiry model (BAKDIPA) to improve among pre-service elementary teachers. The study employed a Research and Development (R&D) design using the Plomp model, consisting of Investigation, Design, and Realization phases. The participants included 33 students in the experimental class and 35 students in the control class enrolled in a Basic Science Concepts course. Data were collected using validation sheets, SPS test instruments, and practicality questionnaires. Experts and practitioners assessed the validity of the developed product, while its practicality and effectiveness were examined through field implementation. The validation results revealed a high level of validity with overall mean scores of 4.10 for the Semester Learning Plan and 4.27 for instructional materials, categorized as “very valid”. Practicality assessment also indicated positive user responses, confirming that the material was feasible to implement. The effectiveness test using a paired t-test indicated a significant improvement in SPS, where the tcount (14.5) > ttable (2.87). The normalized gain analysis further showed an N-Gain of 0.813, categorized as medium effectiveness, while the distribution of SPS levels demonstrated that more students in the experimental class achieved high proficiency compared to the control class. In conclusion, the BAKDIPA instructional material is valid, practical, and effective for enhancing SPS in Basic Science learning for pre-service elementary teachers. This research provides a promising contribution toward strengthening inquiry-oriented science education in teacher preparation programs.